Risk Factors for New-Onset Diabetes Mellitus in Patients Receiving Protease Inhibitor Therapy - Christine A Hughes; Richard P Cashin; Dean T Eurich; Stan Houston (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Metabolic complications including diabetes mellitus (DM) have been associated with protease inhibitor (PI) therapy. Risk factors for the development of DM are not well-defined.